Spatial coding in aging and Alzheimer's disease - Fang, Yue (Nanyang Technological University, 2023)
Spatial memory declines in normal aging while the decline manifests much more severely during aging of Alzheimer’s disease (AD). As the function of the hippocampus in encoding spatial memory is gradually revealed, it remains unclear how the effects of aging and AD on hippocampal spatial coding compare to each other. In my thesis, I am addressing this question by comparatively examining the effects of aging and AD on hippocampal spatial coding in mice. To investigate how aging and AD affect spatial coding, I characterised both control and AD model mice across different ages. These AD model mice have 3 human AD-related mutations in their App gene. I found aging and AD exert distinct effects on hippocampal spatial coding in neuron populations and further revealed aging and AD differentially attack multiple single-neuron properties. The combination effects of aging and AD give rise to a severe spatial coding decline in aged AD mice. These results may provide neuronal-level and populational-level mechanisms to explain the different severity of spatial memory decline in the elderly and AD patients.